APPLICATION OF LEAN MANAGEMENT PRINCIPLES IN THE IDENTIFICATION OF WASTES AND IMPROVING WAITING TIME AT A HOSPITAL PHARMACY. - Gabrielle, Kezia (International Journal of Public Health & Clinical Sciences (IJPHCS))
Background: Pharmacy held a significant role in forming patient's perceived quality of hospital services as a whole due to 80% of patient visits were related to medication procurement. The time of the National Health Insurance (JKN) outpatient non-compounded medication service of Menur Mental Hospital still has not reached the targeted 30 minutes, which according to Lean Thinking, could have been caused by interruption of waste hence further identification was necessary. This study aims to identify 8 types of waste on the JKN outpatient non-compounded medication service. Materials and Methods: Observational descriptive study with a cross-sectional design using primary data sources, consisted of the process of the service and interviewees; and secondary data sources, consisted of relevant published research results and literature. Data were analysed using current-state mapping, identification of value-added, identification of types of waste, identification of causes of waste, and future-state mapping. Result: The average waiting time was 76.59 minutes, with a total of 48 activities, 43.75% value-added, 25.9% necessary non-value-added, 74.1% unnecessary non-value-added or waste. Waste including 1 defect, 2 transportation, 9 waiting, 3 motion, 3 overprocessing, and 1 human potential. Causes of waste including 1 machine factor, 1 technology factor, and 3 environmental factors. Designed process post waste minimisation showed a decrease by 69.1% in waiting time, with a total of 20 activities. Conclusion: There were 6 out of 8 types of waste found on the process which could be minimised through improvements on their factors, namely an upgrade of computer specifications, integration between hospital management information system with INA-CBG's system, placement of printer according to forward grip reach, placement of connector window or preparation tables according to forward grip reach, and addition of scheduling feature on printer system.